Glucose utilisation during status epilepticus in an epilepsy model induced by pilocarpine: a qualitative study - Scorza Fulvio Alexandre; Arida Ricardo Mario; Priel Margareth Rose; Calderazzo Lineu; Cavalheiro Esper Abrão (Arquivos de Neuro-Psiquiatria)
Status epilepticus (SE) is a medical emergency and it is associated to brain damage. 2-deoxy-[14C] glucose (2-DG) procedure has been used to measure the alterations in the functional activity of the brain induced by various pharmacological and toxicological agents. The aim of this study was to determine which changes occur in the seizure anatomic substrates during the SE induced by pilocarpine (PILO) using [14C]-2 deoxyglucose functional mapping technique. Wistar male adult rats were submitted to SE PILO-induced for 6h and received [14C] 2-deoxyglucose injection via jugular vein 45 min before the 6th hour of SE. The control animals were submitted to all procedures but received saline and not pilocarpine. Brain sections were prepared and exposed X-ray film about seven days. The optical density of each region was obtained using a solid state digital analyser. The analysis revealed that 14C-2DG utilisation was pronounced in the SE rats on the areas corresponding to the hippocampal formation (+50.6%), caudate-putamen (+30.6%), frontoparietal cortex (+32.2%), amygdala (+31.7%), entorrinal cortex (+28.2%), thalamic nucleus (+93.5%), pre-tectal area (+50.1%) and substantia nigra (+50.3%) when compared to control. Our results suggest that the different activation levels of the distinct structures may be particularly important for understanding triggering and spreading mechanisms underlying epileptic activity during status epilepticus.